Visual essay - Custódio, Juliano (Guará Journal, 2025)
The images in this edition of Guará are from the II Integrated Extension Conference of the Federal University of Espírito Santo, which took place between November 12th and 14th, 2014. In this visual essay, specifically, photographer Juliano Custódio captured images of a performance by the children’s congo band São Benedito and São Sebastião.